The Effect of Product Quality, Price Perception on Purchasing Decisions with Purchase Intention as Mediating - Utami, Rizka Nurul; Muslikh; Oktavia, Dinda (SAN Scientific, 2024)
This study aims to determine the effect of product quality and price perception on purchasing decisions through buying interest as a mediation on Yamaha motorcycle consumers in Jabodetabek and their understanding from an Islamic point of view. The sampling technique used is purposive sampling. Data were collected using a survey method with a questionnaire instrument. The data analysis method used is Partial Last Square Structural Equation Modeling (PLS-SEM) analysis. The results show that product quality has a positive and significant effect on purchasing decisions, and price perceptions have a positive and significant effect on purchasing. Decisions and product quality have a positive and significant effect on buying interest and price. Perceptions have a positive and significant effect on buying interest, and purchase intentions have a positive and significant effect on purchasing decisions; buying interest can mediate the effect of product quality on purchasing decisions, and buying interest mediates the effect of price perceptions on purchasing decisions. Managerial implications of the relationship between product quality, price perception, purchasing decisions, and the mediating role of purchase intention. In today's competitive market, understanding the factors that influence consumers' purchasing decisions is crucial for businesses to devise effective marketing strategies.